Voltammetry of oxygen in the room-temperature ionic liquids 1-ethyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide and hexyltriethylammonium bis((trifluoromethyl)sulfonyl)imide: One-electron reduction to form superoxide. Steady-state and transient behavior in the same cyclic voltammogram resulting from widely different diffusion coefficients of oxygen and superoxide - Buzzeo, M; Klymenko, O; Wadhawan, J; Hardacre, C; Seddon, K; Compton, R (2003)
The electrochemical reduction of oxygen in two different room-temperature ionic liquids, 1-ethyl-3-methylimidazolium bis((trifluoromethyl)sulfonyl)imide ([EMIM][N(Tf)2]) and hexyltriethylammonium bis-((trifluoromethyl)sulfonyl)imide ([N6222][N(Tf)2]) was investigated by cyclic voltammetry at a gold microdisk electrode. Chronoamperometric measurements were made to determine the diffusion coefficient, D, and concentration, c, of the electroactive oxygen dissolved in the ionic liquid by fitting experimental transients to the Aoki model. [Aoki, K.; et al. J. Electroanal. Chem. 1981, 122, 19]. A theory and simulation designed for cyclic voltammetry at microdisk electrodes was then employed to determine the diffusion coefficient of the electrogenerated superoxide species, O2·-, as well as compute theoretical voltammograms to confirm the values of D and c for neutral oxygen obtained from the transients. As expected, the diffusion coefficient of the superoxide species was found to be smaller than that of the oxygen in both ionic liquids. The diffusion coefficients of O2 and O2·- in [N6222][N(Tf)2], however, differ by more than a factor of 30 (DO2 = 1.48 × 10-10 m2 s-1, DO2·- = 4.66 × 10-12 m2 s-1), whereas they fall within the same order of magnitude in [EMIM]-[N(Tf)2] (DO2 = 7.3 × 10-10 m2 s-1, DO2·- = 2.7 × 10-10 m2 s-1). This difference in [N6222][N(Tf)2] causes pronounced asymmetry in the concentration distributions of oxygen and superoxide, resulting in significant differences in the heights of the forward and back peaks in the cyclic voltammograms for the reduction of oxygen. This observation is most likely a result of the higher viscosity of [N6222][N(Tf)2] in comparison to [EMIM][N(Tf)2], due to the structural differences in cationic component.